Magnetic performance change of multi-main-phase Nd–Ce–Fe–B magnets by diffusing (Nd, Pr)Hx. (12th January 2018) - Ma, Tianyu; Zhang, Wenying; Peng, Baixing; Liu, Yongsheng; Chen, Yongjie; Wang, Xinhua; Yan, Mi
Abstract: The grain boundary diffusion process (GBDP) is effective to enhance coercivity of the single-main-phase (SMP) RE2 Fe14 B (rare earth (RE)) magnets through forming magnetic hardening shells surrounding the hard grain cores. Here, the GBDP was applied to the multi-main-phase (MMP) (Nd, Pr)22.3 Ce8.24 Febal M1.0 B1.0 (wt.%) magnets prepared by sintering the mixture of Ce-free and Ce-containing 2:14:1 powders, which have shown superior magnetic properties, especially coercivity, to the SMP ones at the same average composition. The remanence of the (Nd, Pr)H x diffused magnets increases gradually with the increase of diffusion temperature from 480 to 880 °C, the coercivity, however, slightly decreases. The highest ( BH )max of 350.1 kJ m −3 is achieved when diffusing at 680 °C, which is 9.2% higher than 320.7 kJ m −3 for the as-prepared magnet. The remanence increment is due to the diffusion of Nd/Pr into the 2:14:1 phase grains, enlarging the intrinsic saturation magnetic polarization. The slight coercivity reduction is due to the gradual homogenization of RE distribution within the 2:14:1 grains of the undiffused parts, i.e. approaching the 'close to equilibrium (or SMP)' state, which offsets the positive contributions from the enrichment of Nd/Pr in the Ce-rich 2:14:1 phase and the formation of continuous RE-rich intergranular phase. These findings suggest that the GBDP effect on coercivity of the MMP Nd–Ce–Fe–B magnets is distinctly different from the SMP ones, and that the chemical heterogeneity should be carefully controlled to improve the magnetic properties of such high cost-performance permanent magnets.